EKSEKUSI TERHADAP KREDIT MACET PADA KREDIT PEMILIKAN RUMAH (KPR) DI PT. BANK TABUNGAN NEGARA (PERSERO) KANTOR CABANG YOGYAKARTA - , Budhiman Dwi Santosa ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this research was to find out the execution towards the stagnant credit ini Housing Property Credit in PT. Bank Tabungan Negara (Limited Liability Company) of Branch Office Yogyakarta, to find out the barriers faced in the execution towards stagnant credit in Housing Property Credit as well as to know the efforts conducted by PT. Bank Tabungan Negara (Limited Liability Company) of Branch Office Yogyakarta to solve these barriers. This research is juridical empirical. It is mentioned as juridical by reason in studying the existing problem it is reviewed based on the legal material or regulations relating to the materials of research through literary research to find secondary data. It is mentioned as empirical by reason in this research it is based on field research to gain primary data. The result of this research shows that : (1) The execution towards stagnant credit in Housing Property Credit in PT. Bank Tabungan Negara (Limited Liability Company) of Branch Office Yogyakarta often uses executional prorate by executional auction process of security right through State Property and Auction Service Office (KPKNL) of Yogyakarta. It is the simplest and most efficient way compared to the execution of court verdict that has firm legal power. This execution does not any fiat of the Head of State Court thus it can be conducted individually by PT. Bank Tabungan Negara (Limited Liability Company) of Branch Office Yogyakarta a the holder of first level of security right. (2) The barriers in execution towards stagnant credit in Housing Property Credit in PT. Bank Tabungan Negara (Limited Liability Company) of Branch Office Yogyakarta are mostly caused by the existence of external factor of the Bank. One of them is the disloyal or non-obedience of Debtor in conducting the clauses in the Agreement of Housing Property Credit had been agreed. It is caused by the non-understanding and lack of comprehension of part of Debtor in legal field however it also can be caused by the existence of bad interest. The effort conducted by PT. Bank Tabungan Negara (Limited Liability Company) of Branch Office Yogyakarta to solve the barriers is by conducting diplomacy familiarly and lastly by forceful legal procedures.